Gathering insights of the global scenario of floating-bed agriculture through systematic literature review for its promotion in Indian context - Tanmoy Kumar Ghosh; Ashish Kumar Singh; Sudip Mitra; Sougata Karmakar (Progress in Disaster Science)
India is highly vulnerable to the escalating adversities of global climate-induced disasters, with flooding among the most significant consequences incurring severe detrimental effects on traditional land-based agriculture practices due to prolonged waterlogging. In this context, floating-bed agriculture shows promise for flood-prone and wetland areas, particularly in India, where resilient farming practices are essential. This method offers a viable solution to mitigate climate-induced flooding and promote sustainable agriculture. However, challenges persist, including concerns about instability of floating beds and the risk of crop destruction. This literature review aims to comprehensively document the current global scenario of floating-bed agriculture to promote it in India. Employing the PRISMA framework, a meticulous analysis of published literature on floating agriculture was conducted using reputable search engines (Google Scholar, Web of Science, Scopus). After applying inclusion and exclusion criteria, we selected 48 research articles (published between 1997 and 2023) to include in this review paper. The analysis of 48 articles reveals significant research gaps in floating-bed agriculture, emphasizing the need for exploration by agricultural researchers and engineers. The findings underscore key benefits such as increased crop yields, while also highlighting challenges including optimal crop selection and sustainability aspects. Detailed field research and scientific investigations are essential to ascertain the viability of floating-bed agriculture as a climate-induced disasters adaptation method, fortifying the resilience of farming communities in low-lying, flood-prone, and marshy areas.